Efektifitas Buku Saku Digital untuk Transformasi Pengetahuan dan Sikap Remaja Putri tentang Pencegahan Anemia: The Effectiveness of Digital Pocketbook for the Transformation of the Knowledge and Attitude of Adolescent Girls about the Prevention of Anemia - Nuryana, Hurip; Rachmawati, Emma; Khusun, Helda; Mulyawati, Devi Annisa; Lestari, Hesti (Universitas Airlangga, 2025)
Background: Anemia is a significant health issues among adolescent girls, negatively impacting their life cycle. Bogor City has an anemia prevalence of 28%. The Indonesian Ministry of Health has introduced a digital pocketbook